2021
DOI: 10.1029/2021jc017576
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Intense Thermocline Shear Associated With Wind‐Forced Near‐Inertial Internal Waves in a Summer Stratified Temperate Shelf Sea

Abstract: Thermocline shear (i.e., velocity shear in the thermocline) lies at the heart of stratified shelf sea systems, regulating the vertical mixing and transport of mass and biogeochemical constituents. Based on year‐long moored ADCP measurements in the southern Yellow Sea (YS), the baroclinic kinetic energy and thermocline shear are investigated in this study. The rotary spectra analysis of the velocity measurements and numerical simulations with the slab model demonstrate that the wind‐forced near‐inertial interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In the previous work of Yang et al. (2021), based on year‐long (August 2012–July 2013) moored ADCP measurements in the southern YS, it has been demonstrated that the wind‐induced NIWs can be a quite prevailing phenomenon in the YS during the warm season as a response to frequent wind pluses. Moreover, Yang et al.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In the previous work of Yang et al. (2021), based on year‐long (August 2012–July 2013) moored ADCP measurements in the southern YS, it has been demonstrated that the wind‐induced NIWs can be a quite prevailing phenomenon in the YS during the warm season as a response to frequent wind pluses. Moreover, Yang et al.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, Yang et al. (2021) identified strong near‐inertial responses at the mooring station (121.7°E, 35.8°N, ∼180 km to Stn. C05) during the same period of the 2013 cruise in the present study (14–19 July 2013, see their Figure 9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The slab model used in our study is a linear damped slab model originally proposed by Pollard and Millard (1970). It has been widely used to examine surface near-inertial responses (Pollard, 1980;Martini et al, 2014;Yang et al, 2021;Yang et al, 2023). The governing equation is given by…”
Section: Slab Modelmentioning
confidence: 99%